Kepuasan Pasien terhadap Pelayanan Pendaftaran Rawat Jalan Rumah Sakit Pemerintah: Analisis Kesenjangan Ekspektasi dan Persepsi - Heryana, Ade; Farhana, Najla Kamilia; Nurmawaty, Dwi; Handayani, Rini (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Outpatient registration services represent a critical touchpoint in the patient experience at hospitals. A mismatch between expectations and the actual service delivered can affect patient satisfaction. Public hospitals continue to face complaints related to the registration process, such as long waiting times, unclear information, and inadequate waiting facilities. This study aims to assess patient satisfaction with outpatient registration services by comparing expectations and perceptions based on Expectancy Disconfirmation Theory and by using the Importance Performance Analysis (IPA) method to provide service improvement recommendations. This quantitative study employed an analysis of identically similar characteristics of paired Expectation and Perception 84 patients, using a questionnaire based on the World Health Organization’s seven service quality dimensions. The findings reveal a negative gap between expectation scores (mean = 3.21, CI Lower Bound = 3.0204, Upper Bound = 3.3956) and perception scores (mean = 2.75, CI Lower Bound = 2.5008, Upper Bound = 2.9962). The Wilcoxon Signed Rank Test showed a significant difference (p-value < 0.05) between expectations and perceptions. The IPA analysis indicated that priority service attributes that need to be improved include the availability of waiting chairs, accuracy and speed, attention and empathy, and service discrimination. These results suggest that outpatient registration services in public hospitals have not fully met patient expectations. Therefore, improving service quality in several key attributes is crucial to enhancing patient satisfaction.